The Validity and Reliability of the Online Cooperative Learning Attitude Scales in the Indonesian Language - Elisabeth Rukmini; Arya Susila Nugraha; Hanna Angelina; Dara Aprilia Christianty (Soegijapranata Catholic University, 2021)
Interactive online learning requires students’ cooperation. Online cooperative learning focuses on learning activities on group cohesiveness to achieve the highest cognitive level. Students can improve their teamwork skills, problem-solving skills, social skills, self-confidence, academic success, and metacognition levels through online cooperative learning activities. The Online Cooperative Learning Attitude Scales (OCLAS) scale is a tool to measure students’ attitudes towards online cooperative learning. Education in Indonesia uses Indonesian as the language of instruction. Therefore, the adaptation of measurement tools such as OCLAS into the Indonesian language is crucial. This study aimed to adapt OCLAS into Indonesian by translating the original OCLAS into the Indonesian language and determining the instrument’s validity and reliability. The OCLAS has three main components: positive interdependence, individual accountability, and group processing for equal individual contribution. The original version contained 17 statements with responses using a Likert scale of five and seven points. We validated the OCLAS using the item-correlation method. The reliability was measured using the Cronbach’s Alpha method, which is useful for measuring internal consistency. The original OCLAS was translated into the Indonesian Language. A language center in a prominent university performed the verification of forward and backward translation of the Indonesian OCLAS. The Indonesian-OCLA was distributed to 59 students at a private university from the pharmacy and non-pharmacy study programs and 275 high school students. The validation results showed seven invalid items for pharmacy students, five invalid items for non-pharmacy students, and six invalid items for high school students. The Indonesian-OCLAS has Cronbach’s Alpha reliability with a value of 0.711 for pharmacy students, 0.791 for non-pharmaceutical students, and 0.702 for high school students. This study showed that ten out of 17 statements had good validity, and they were reliable. Therefore, we recommended the usage of the Indonesian-OCLAS toward high school and college students.